2020
DOI: 10.3390/cancers12092593
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Functional Regulation of TRIB1 Contributes to Prostate Cancer Pathogenesis

Abstract: Prostate cancer is the most frequent malignancy in European men and the second worldwide. One of the major oncogenic events in this disease includes amplification of the transcription factor cMYC. Amplification of this oncogene in chromosome 8q24 occurs concomitantly with the copy number increase in a subset of neighboring genes and regulatory elements, but their contribution to disease pathogenesis is poorly understood. Here we show that TRIB1 is among the most robustly upregulated coding genes within the 8q2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…For example, TRIB1 also accelerates degradation of C/EBPα in AML cells [ 98 ]. In addition, TRIB1 is also involved in the etiology of glioma [ 99 ], liver [ 100 ] and prostate cancer [ 101 ]. Regarding TRIB3, its expression was found elevated in patients with colorectal cancer and its expression correlated with poor overall survival [ 102 ].…”
Section: The Emerging Role Of Trib2 In Therapy Resistancementioning
confidence: 99%
“…For example, TRIB1 also accelerates degradation of C/EBPα in AML cells [ 98 ]. In addition, TRIB1 is also involved in the etiology of glioma [ 99 ], liver [ 100 ] and prostate cancer [ 101 ]. Regarding TRIB3, its expression was found elevated in patients with colorectal cancer and its expression correlated with poor overall survival [ 102 ].…”
Section: The Emerging Role Of Trib2 In Therapy Resistancementioning
confidence: 99%
“…Shahrouzi et al found that the expression of TRIB1 in the prostate of mice with PCa ( Pten pc-/- ) was higher than in wild-type controls ( Pten pc+/+ ). They then developed a Cre-dependent TRIB1 transgenic mouse model, in which the incidence of PCa was increased in Pten pc+/- mice from 16.7% to 50% 41 . Additionally, TRIB1 participates in the endoplasmic reticulum pathway and is required for the expression of the endoplasmic reticulum partner GRP78, which is closely related to the occurrence of prostate tumors 36 .…”
Section: Trib1 and Cancermentioning
confidence: 99%
“…Notably, TRIB1 protein levels are relatively high in the PC3 cell line, whereas COP1 is undetectable, raising the question whether COP1 under specific stimulatory conditions may mark TRIB1 for proteasome-mediated degradation. Increasing TRIB1 expression in these PC3 cells has been shown to promote tumour growth [ 58 ], whereas increasing TRIB1 in DU145 cells did not [ 59 ]. Consequently, we keenly await proteomic analyses of the TRIB-interactome in the COP1-less PC3 cells, as well as structural studies that define the effects of TRIB1-captured protein substrates on the release of its sequestered C-terminal COP1-binding motif.…”
Section: Growth Of Trib (And Cop1) Researchmentioning
confidence: 99%
“…Returning to the TRAIN tool-box, this includes a series of scripts to interrogate and visualise genomic data, plasmid and viral constructs, and murine models to study the physiological roles of cell-specific TRIB1 and TRIB3 expression, for example, in myeloid cells [ 70 ], prostate-specific Pten -deficient mice [ 59 ] and Tregs ( Trib1 KO , richard.danger@univ-nantes.fr ; sophie.brouard@univ-nantes.fr ). Finally, we would like to thank the wider TRIB community for their contribution to student TRAIN training events and bi-annual international TRIB conferences.…”
Section: Growth Of Trib (And Cop1) Researchmentioning
confidence: 99%